Using educational drama to improve outcomes for looked-after children - Will Barlow (Scottish Journal of Residential Child Care)
Educational attainment has long been seen as a strength factor in building the resilience of young people. This paper builds upon the work of Stevens, Kirkpatrick and McNicol (2008) and suggests that Educational Drama could have a positive effect on the literacy attainment of looked-after children in Scotland.